QUALITY CONTROL X RAYS MAMMOGRAPHY IN THE EFFORT MITIGATION INCREASING NUMBER OF CANCER PATIENTS - Rini Safitri; Evi Yufita (Universitas Syiah Kuala, 2017)
Abstract. Early detection of breast cancer is the first step in prevention that can be done by women, therefore when one is diagnosed with breast cancer, the appropriate treatment can be performed quickly and accurately. Early diagnosis of breast cancer can be a way of mitigation in preventing breast cancer through the use of mammography. Bureau of Radiology as said by The Joint Commission on Accreditation of Hospitals (JHCA) stated that one of the responsibilities of the radiology unit is to control the quality of service which aims to minimize the radiographic image repetition factor; as well as maximizes the quality of radiographic image. Quality control tests are an effort that is needed on the mammography X-ray diagnostics tools. This is done to maintain the quality of expected output. The parameters that are included within the radiation output are the magnitude of current and the voltage of tube that are produced; therefore they remained constant and correspond to the recommended standard. Bureau of Radiological Health, as said by JHCA mentioned that to control the quality of image which will minimize the radiographic image repetition and maximizes the quality of radiographic image. Therefore the radiation output will not be dangerous later. The early stage of the quality control test on the machine was conducted by setting all the filtrations which were placed to capture the x-ray on the x-ray plane tube with minimum value. Then, ionization chamber is placed on the test subject points; right after that the distance between it to the radiation source is noted. The x-ray film is place on a film on the compression table of the patient and the distance between film and the focus point is noted. This is then exposed using a target filter Mo/Mo by setting the current as well as variation the voltage and time. The standard voltage measurements are 20-33kVp. This data is from the observations of time exposure; the output value is then noted. The above procedure is conducted from the minimum voltage to the maximum voltage. The output ray is measured for each voltage. The same procedure is conducted to the target filter Mo/RH. The results obtained are that the greater the input voltage and current will subsequently produce greater doses, therefore the exposure has exceeded the standard limit 0.1 mHy with longer exposure time. The HVL density thickness on the mammography X-ray machine determined the quality of the beam and the doses of x-ray exposure on the mammography machine. The output stability of x-ray beam exposure in the mammography machine mode Mo/Mo still fulfill the standard which is the value of 69% Keywords: Quality Control, Sinar-X, mammography, Mp/Mo, Mo/RH